Pemanfaatan Kapang Aspergillus niger sebagai Inokulan Fermentasi Kulit Kopi dengan Media Cair dan Pengaruhnya Terhadap Performans Ayam Broiler - Akmal, Akmal; Filawati, Filawati (Fakultas Peternakan Universitas Jambi, 2008)
During the study, it was used 100 broiler aged 7 days and 5 treatment ration which contain different fermented coffee pulp. The design used in this study was the block randomized design (BRD) with 5 treatmens. Parameter measured were ration consumption, weight growth, and ration conversion. The result of this study showed that the use of fermented coffee pulp in the ration was significantly effective (P<0,05) on the weight growth, ration consumption and ration conversion. It could be concluded that fermented coffee pulp can be used up to 10% in the ration of the broiler